Las ‘Fiebres del Magdalena’: medicina y sociedad en la construcción de una noción médica colombiana, 1859-1886 (2007)
In this article, I explore the theoretical, social and ideological bases of the emergence and consolidation of the Colombian medical notion of the 'Magdalena fevers'. Firstly I show how, in the late 1850s, the emerging Colombian body of medical doctors elaborated peculiar notions on fevers by articulating the European medical theories (i.e. the miasmatic theory and the climatic determination of diseases) with the negative valuation of the hot climate. Secondly, I explain how free trade policies in the mid-1800s, and the economic and ideological impacts of the agricultural export of tobacco and indigo determined doctors' interest in the epidemics occurring in the production centers and also, therefore, the emergence of the notion of 'Magdalena fevers'. I also show how doctors established a causal association between the productive process of those goods and the fevers.